The Toddler's Fracture. Issue 1 (January 2022) - Wang, Yiqiao; Doyle, Meagan; Smit, Kevin; Varshney, Terry; Carsen, Sasha
Abstract : Objective: The tibial toddler's fracture is an important diagnosis in both emergency and urgent care, presenting as acute onset lower extremity pain or limping in a young child. Diagnosis and management may be challenging because of an extensive differential diagnosis. The objectives of this study were to provide an overview of the toddler's fracture and to guide clinicians by summarizing up to date literature for both diagnosis and management this common condition. Methods: This study analyzed literature from the PubMed database from the years of 1964 to 2018. The main focus was on the diagnosis and management of the toddler's fracture. Results: This review demonstrates that diagnosis is primarily made through history and physical examination, as radiographs are often negative at initial presentation. Treatment involves a short period of immobilization, which can be facilitated through the use of a cast, a splint, or no external support. Successful healing and a full return to normal activities and development are near universal. Conclusions: Although a stable fracture with an excellent prognosis, opportunities exist to improve toddler's fractures diagnosis and treatment protocols, to optimize clinical management.